2007
DOI: 10.1111/j.1365-2486.2007.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the δ13C of foliage of Pinus sylvestris L. in relation to climate and additions of nitrogen: analysis of a 32‐year chronology

Abstract: We report an analysis of both the long-and short-term drivers of the carbon (C) isotope composition (d 13 C) values of current year needles of Pinus sylvestris L. linked to changing atmospheric carbon dioxide (CO 2 ) concentrations (c a ) and climate using data from a uniquely long-term nitrogen (N) fertilization experiment in the north of Sweden (consisting of three N dosage levels and a control treatment) from 1970 until 2002. N loading produced trees with less negative d 13 C of foliage, by around 0.45% on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 50 publications
4
45
3
1
Order By: Relevance
“…These results suggest that other factors, especially drought, may have influenced tree response to increasing C a Xu et al 2013). Such phenomenon was not taken into consideration in the current models, which predict a continuing rise in terrestrial carbon storage as a result of the combined effects of CO 2 fertilization and climate change with the rising C a (Betson et al 2007;Leuzinger and Körner 2007). Therefore, if a long-term reduction in sensitivity to atmospheric CO 2 exists among large proportion of trees in the temperate regions, the degree of future terrestrial carbon storage would have been overestimated (Peñuelas et al 2008).…”
Section: Time-dependent Variations In Iwue and Baimentioning
confidence: 67%
“…These results suggest that other factors, especially drought, may have influenced tree response to increasing C a Xu et al 2013). Such phenomenon was not taken into consideration in the current models, which predict a continuing rise in terrestrial carbon storage as a result of the combined effects of CO 2 fertilization and climate change with the rising C a (Betson et al 2007;Leuzinger and Körner 2007). Therefore, if a long-term reduction in sensitivity to atmospheric CO 2 exists among large proportion of trees in the temperate regions, the degree of future terrestrial carbon storage would have been overestimated (Peñuelas et al 2008).…”
Section: Time-dependent Variations In Iwue and Baimentioning
confidence: 67%
“…Nevertheless, some studies are not found this trend (e.g. Marshall and Monserud, 1996;Beston et al, 2007).…”
Section: Causes Of Iwue and The Physiological Implications Of The Isomentioning
confidence: 85%
“…They noted that while leaf area significantly increased in response to fertilization, fine root area necessary for water uptake did not, causing the root area : leaf area ratio in fertilized trees to be half that of control trees. Betson et al (2007) found that the variation in needle d 13 C over time in fertilized trees was more sensitive to climatic variation than control trees, implying that this sensitivity was an increased susceptibility to drought in fertilized trees. No significant differences between treatments were found for earlywood.…”
Section: Forest Fertilization Responsesmentioning
confidence: 92%